When Truths Collide: Christian Privilege Undermines Freedom of Identity in Canadian Public Schools - Surette, Tanya (Alberta Journal of Educational Research, 2022)
The conflict between freedom of religion and freedom of identity and expression in schools remains a controversial topic internationally. As primarily socializing agents, schools reproduce the cultural norms of the communities within which they are embedded. When schools are situated in environments with high levels of religiosity that are non-affirming to gender and sexually diverse youth, the impact is felt within the lived curriculum of individual students. Using narrative inquiry, this study explored this impact and student perceptions of how freedom of religion became a means to justify discrimination and oppression of sexual and gender diverse students and promoted feelings of insecurity and isolation amongst this marginalized group. Key words: Christian privilege; freedom of religion; gender and sexual minority; secondary schools Le conflit entre la liberté de religion et la liberté d'identité et d'expression dans les écoles demeure un sujet de controverse à l'échelle internationale. En tant que principaux agents de socialisation, les écoles reproduisent les normes culturelles des communautés dans lesquelles elles sont intégrées. Lorsque les écoles sont situées dans des environnements à haut niveau de religiosité qui ne sont pas favorables à la diversité sexuelle et de genre des jeunes, l'impact est ressenti dans le curriculum vécu de chaque élève. En utilisant une enquête narrative, cette étude a exploré cet impact et les perceptions des élèves sur la façon dont la liberté de religion est devenue un moyen de justifier la discrimination et l'oppression des élèves sexuellement et sexuellement différents et a favorisé les sentiments d'insécurité et d'isolement parmi ce groupe marginalisé. Mots clés: privilège chrétien ; liberté de religion ; minorité sexuelle et de genre ; écoles secondaires